Empirical research on project implementation success and change management practices in Malaysian Government-Linked Companies (GLCs) - S. Basamh, Saeed; Huq, Md.Najibul; Ahmad Dahlan, Abdul Rahman (IRPN Publishers, 2013)
The purpose of this empirical study is to address the practices of project change management in the context of Government-Linked Companies (GLCs) in Malaysia, focusing on Project Managers (PMs), Project Team Members (PTMs), Change Managers (CMs) and any other Top Managers involved in a project. Also, checking the validity of a number of critical success factors from the Project Implementation Profile (PIP) in the context of GLCs in Malaysia. PIP is a comprehensive managerial tool introduced by Pinto’s and Slevin and later was enhanced and re-tested by study done by Belout and Gauvereau. Government-linked companies were previously government agencies or public enterprises established to provide services for social purposes. The Malaysian Government considers the importance of the Government-linked companies (GLCs) role. Critical success factors (or CSFs) are the actions and processes that can be controlled or affected by management to achieve the goals set by an organization. Based on the responses, we have come to understand that the GLCs surveyed have the highest focus on the success factor “Client Acceptance”, followed by “Communications”, indicating that they are more compliant towards the best practices in those aspects. However, certain facets like “Human Resources” (resource allocation) and “Top Management Support” were found to require more concentration in order to be more compliant to the best practices, and resolve certain Project Team expectations. The findings are discussed and avenues for further research proposed.